Experiences and barriers related to breastfeeding among Nigeria immigrant mothers living in Kuala Lumpur Malaysia - a qualitative study - Omoyemi, Bolarinwa Balikis; Leong, Ong Swee; Abdullah, Khatijah Lim; Mat Azmi, Intan Suhana Munira; Lam, Soh Kim; Geok, Soh Kim; Omolabake, Zakariyah Ummulkhair (Horizon Research Publishing, 2024)
Background: Breastfeeding plays a crucial role in promoting optimal health and development for infants. However, immigrant populations often encounter unique challenges that can hinder successful breastfeeding practices, such as language barriers, lack of social support, and unfamiliarity with healthcare systems. Despite this pressing issue, limited research has been conducted on the specific experiences and barriers faced by immigrant mothers in Malaysia, particularly those originating from Nigeria. Objectives: In this research, we conducted a qualitative study to explore the experiences and barriers related to breastfeeding among Nigerian immigrant mothers residing in Kuala Lumpur, Malaysia. Methods: A descriptive qualitative approach was used to explore the in-depth experiences of mothers using semi-structured interview guide through purposive sampling. Face to face interview was conducted at the home of the participant (n=12). The interview was recorded, transcribed, and analyzed using induced content analysis. Results: Our study sample comprised 12 mothers aged between 17 and 45 years. Thematic analysis of the interviews revealed 2 primary themes: breastfeeding practices and barriers to breastfeeding. Within these themes, we identified 11 sub-themes, encompassing aspects such as importance of breastfeeding initiation, duration, exclusivity, socioeconomic factors, language barriers, lack of support, limited knowledge, postpartum stress, feelings of embarrassment, and misconceptions. Conclusions: Our findings underscore the significant impact of breastfeeding barriers on the practices of Nigerian immigrant mothers in Malaysia. We recommend that healthcare professionals and relevant stakeholders extend support to this population, including the provision of affordable and accessible healthcare services, as well as the availability of trained interpreters to overcome language barriers. These insights can guide the development of targeted interventions aimed at improving breastfeeding rates and fostering the overall well-being of immigrant mothers and their infants. Copyright©2024 by authors, all rights reserved. Authors agree that this article remains permanently open access under the terms of the Creative Commons Attribution License 4.0 International License.